2013
DOI: 10.1002/app.38948
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(ϵ‐caprolactone‐cop‐dioxanone)–poly(ethylene glycol)–poly(ϵ‐caprolactone‐cop‐dioxanone)/bioactive inorganic particle nanocomposites

Abstract: With an aim to develop injectable hydrogel with improved solution stability and enhanced bone repair function, thermogelling poly(e-caprolactone-co-p-dioxanone)-poly(ethylene glycol)-poly(e-caprolactone-co-p-dioxanone) (PECP)/bioactive inorganic particle nanocomposites were successfully prepared by blending the triblock copolymer (PECP) with nano-hydroxyapatite (n-HA) or nano-calcium carbonate (n-CaCO 3 ). The hydrogel nanocomposites underwent clear sol-gel transitions with increasing temperature from 0 to 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The same authors have reported other works dealing with the copolymerization of DX with lower amounts of CL and using Al­(O i Pr) 3 as an initiator (i), mainly for the synthesis of semicrystalline diblock copolymers. , The synthesis of multiblock copolymers obtained by the coupling of oligo­(CL) and oligo­(DX) as shape memory thermoplastic materials for the fabrication of sutures has also been described . The copolymerization of CL and DX has been reported infrequently in the literature, and patents and patent applications have suggested diblock or segmented copolymers consisting of more DX than CL that can be utilized to manufacture soft sutures. While the random copolymerization of CL and DX has been reported once, thermogelling triblock copolymers consisting of low-molecular-weight CL/DX random segments and poly­(ethylene glycol) were described by the same authors as suitable for drug delivery applications. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors have reported other works dealing with the copolymerization of DX with lower amounts of CL and using Al­(O i Pr) 3 as an initiator (i), mainly for the synthesis of semicrystalline diblock copolymers. , The synthesis of multiblock copolymers obtained by the coupling of oligo­(CL) and oligo­(DX) as shape memory thermoplastic materials for the fabrication of sutures has also been described . The copolymerization of CL and DX has been reported infrequently in the literature, and patents and patent applications have suggested diblock or segmented copolymers consisting of more DX than CL that can be utilized to manufacture soft sutures. While the random copolymerization of CL and DX has been reported once, thermogelling triblock copolymers consisting of low-molecular-weight CL/DX random segments and poly­(ethylene glycol) were described by the same authors as suitable for drug delivery applications. , …”
Section: Introductionmentioning
confidence: 99%
“…28−30 While the random copolymerization of CL and DX has been reported once, 31 thermogelling triblock copolymers consisting of low-molecular-weight CL/ DX random segments and poly(ethylene glycol) were described by the same authors as suitable for drug delivery applications. 32,33 We wanted to develop a polymer that was suitable for the fabrication of tissue engineering scaffolds by three-dimensional (3D) printing with enhanced properties relative to PCL-based polymers and the use of which could be approved in biomedical applications. We reasoned that by random copolymerization of CL with a lower amount of DX we could develop degradable polymers that were suitable for the fabrication of scaffolds and that could be processed in a manner similar to that for PCL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…HA-containing nanocomposites were produced by mixing a stable nano-HA sol with sol-gel bioglasses (Ragel et al 2002;Valenzuela et al 2012) or polymers (Alves Cardoso et al 2012;Dessı et al 2012;Chen and Hao 2013;Demirel and Aksakal 2015). The sol-gel synthesis of TiO 2 -HA composites was reported (Milella et al 2001;Im et al 2007).…”
Section: Composite Biomaterialsmentioning
confidence: 98%